Five new species of the feather mite genus Trouessartia Canestrini from South America (Acari: Trouessartiidae) - Hernandes, Fabio Akashi (Zootaxa, 2014)
Five new feather mite species of the genus Trouessartia Canestrini are described from South American birds: Trouessartia latiducta sp. nov. from Phylloscartes kronei (Tyrannidae), T. basileuteri sp. nov. from Basileuterus culicivorus (Parulidae), T. sicaliae sp. nov. from Sicalis flaveola (Emberizidae), T. savanae sp. nov. from Tyrannus savana (Tyrannidae), and T. picumni from Picumnus fulvescens (Picidae). The latter species is the first representative of the genus described from a bird of the order Piciformes.